Assessment of Executive Functions in Prader–Willi Syndrome and Relationship with Intellectual Level. Issue 4 (20th April 2013) - Chevalère, J.; Postal, V.; Jauregui, J.; Copet, P.; Laurier, V.; Thuilleaux, D.
<x xml:space="preserve">Abstract</x> Introduction The aim of the present study was to determine whether individuals with Prader–Willi syndrome (PWS) have impaired global executive functioning and whether this deficit is linked with intellectual disability. Another objective focussed on the variability in performance of intellectual quotient (IQ) and executive functions (EF) depending on the genotypic subtype. A final objective investigated whether the relationships between IQ and EF are different according to the genotypic subtype. Method Twenty individuals with PWS and mild‐to‐moderate IQ (standard scores between 55 and 90, age range 19 and 49 years old, SD = 28.1) were administered an ecological battery of executive functioning (behavioural assessment of dysexecutive syndrome, BADS, adapted from Wilson et al. (1996) Behavioural Assessment of the Dysexecutive Syndrome. Thames Valley Test Company: Bury St Edmunds, UK.). The BADS contains six tests evaluating EF. The sample comprised 14 deletion subtype and six maternal uniparental disomy (m‐UPD) subtype. Results Behavioural assessment of dysexecutive syndrome scores were below the level of the standardized healthy populations of the battery and equivalent to those of the neuropathological standardized population. Most scores on EF tasks were relatively highly correlated with Full Scale and Verbal IQs but were not significant or moderately correlated with Performance IQ. Lastly, underlying differences were found in scores on two EF tasks (the Rule Shift Card and the Zoo Map subtests) between the deletion and m‐UPD subtypes. Discussion These data suggest a deficit of executive functioning in PWS that is linked more with verbal skills than performance skills. They also suggest that the impact on executive functioning may differ according to the genotype.